Commercial active packaging maintaining physicochemical qualities of carambola fruit during cold storage. (June 2022) - Nimitkeatkai, Hataitip; Techavuthiporn, Chairat; Boonyaritthongchai, Panida; Supapvanich, Suriyan
Abstract: Physicochemical quality of carambolas kept in active packaging during storage at 10 °C for 35 d were investigated. The carambola was individually packaged in a low density polyethylene (LDPE) bag with and without a sachet of commercial oxygen and ethylene absorbers. Fruit weight, color, ascorbic acid, firmness and the activities of polygalacturonase (PG) and pectin methylesterase (PME) were monitored. Storage in the active packaging reduced the losses of fruit weight and ascorbic acid content as well as maintained fruit color over the storage. The fruits packed in the active packaging had higher firmness compared to control. Negative relationships between softening and both of the PG ( R 2 = 0.6803) and PME ( R 2 = 0.8179) activities were found. These concluded that the active packaging effectively maintained quality of carambolas. Highlights: Commercial O2 and C2 H4 absorbers were used in packed carambola fruit. Active packaging delayed losses of weight and ascorbic acid and changes in color. Firmness was better maintained using active packaging. Correlation between softening and PG and PME activities in carambola was found.